Effects of corticosteroid plus long-acting beta2-agonist on the expression of PD-L1 in double-stranded RNA-induced lung inflammation in mice. Issue 1 (December 2017) - Hamano, Saaka; Matsumoto, Koichiro; Tonai, Ken; Fukuyama, Satoru; Kan-o, Keiko; Seki, Nanae; Inoue, Hiromasa; Nakanishi, Yoichi
Abstract Background Airway viral infections cause the exacerbations of asthma and chronic obstructive pulmonary disease. PD-L1, also known as B7-H1, is an immune-checkpoint molecule that plays a role in an escape mechanism of viruses from the host immune systems. This escape may be associated with the persistence of viral infection and the exacerbation of the underlying diseases. In a study in vitro, we have shown that corticosteroids plus long-acting beta2 -agonists (LABAs) attenuate the upregulation of PD-L1 on airway epithelial cells stimulated with an analog of viral double-stranded RNA, polyinosinic-polycytidylic acid (poly I:C). To address its biological relevance in vivo, we investigated the effect of corticosteroid plus LABA on the expression of PD-L1 in double-stranded RNA-induced lung inflammation in mice. Methods Mice were intratracheally administered with poly I:C. The expression of PD-L1 on the lung cells was assessed by flow cytometry and inflammation was assessed for bronchoalveolar lavage fluid (BALF). Independent as well as combination effects of ciclesonide and indacaterol were examined. Results Administration of low dose poly I:C upregulated the expression of PD-L1, induced neutrophilia and increased keratinocyte-derived chemokine (KC), macrophage inflammatory protein-1β (MIP-1β), and IL-6 in BALF. The upregulation of PD-L1, neutrophilic inflammation and increase of KC were suppressed by ciclesonide plus indacaterol, but not by either when administered independently. Although the upregulation of PD-L1 by high dose poly I:C was suppressed by ciclesonide plus indacaterol, neutrophilia and increased KC, MIP-1β, and IL-6 in BALF were not attenuated. Conclusions Ciclesonide plus indacaterol attenuate double-stranded RNA-induced upregulation of PD-L1 in the lungs.